2022
DOI: 10.1155/2022/4809313
|View full text |Cite
|
Sign up to set email alerts
|

Using the WSPR Mode for Antenna Performance Evaluation and Propagation Assessment on the 160-m Band

Abstract: In the last couple of years, the use of weak signal propagation reporter (WSPR) has grown significantly in the radio amateur community and beyond. This protocol allows to probe potential propagation paths between radio transceivers, operating at a low-power level. The protocol decodes the received signals and translates them into appropriate signal-to-noise ratio levels, which reveal the possible propagation paths between the transmitter and receiver using ionospheric reflections. In this article, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Using amateur radio data, multiple peer-reviewed studies have been published. These include studies of the ionospheric impacts of solar flares and geomagnetic storms [17,13,51], traveling ionospheric disturbances (TIDs) [20], Sporadic E [8,7], near vertical incidence skywave (NVIS) propagation [46,47,48,51,49,50], greyline propagation [31], 160 m band propagation [45], solar eclipses [16], and plasma cutoff and single-mode fading [36]. The current technical capabilities of amateur radio community and future opportunities for scientific and operational advancement are detailed in the companion paper, Frissell et al [19].…”
Section: Amateur Radio and Scientific Discoverymentioning
confidence: 99%
“…Using amateur radio data, multiple peer-reviewed studies have been published. These include studies of the ionospheric impacts of solar flares and geomagnetic storms [17,13,51], traveling ionospheric disturbances (TIDs) [20], Sporadic E [8,7], near vertical incidence skywave (NVIS) propagation [46,47,48,51,49,50], greyline propagation [31], 160 m band propagation [45], solar eclipses [16], and plasma cutoff and single-mode fading [36]. The current technical capabilities of amateur radio community and future opportunities for scientific and operational advancement are detailed in the companion paper, Frissell et al [19].…”
Section: Amateur Radio and Scientific Discoverymentioning
confidence: 99%
“…The use of such data for space weather and space physics research was first demonstrated by Frissell et al [18], who showed a solar flare HF radio blackout observed by the RBN. Subsequent studies have used these systems to study Large Scale Traveling Ionospheric Disturbances (LSTIDs) [24], characterization and prediction of Sporadic E [15,14,3], asymmetries in ionospheric greyline propagation [34], 160 m band propagation [47], geomagnetic storm and solar flare ionospheric impacts [21], plasma cutoff and single-mode fading [38], solar eclipse ionospheric impacts [20], and understanding of localized radio propagation anomalies [43].…”
Section: Global Scale Amateur Radio Observational Networkmentioning
confidence: 99%
“…WSPR rapidly gained popularity among amateur radio operators for its ability to detect very weak signals and report propagation conditions over long distances [2]. Today, WSPR is extensively utilized by amateur radio operators and researchers to study radio propagation and conduct experiments in radio communication, with applications encompassing grayline propagation [3], antenna testing and design [4], and the investigation of solar eclipse effects on radio propagation [5].…”
Section: Introductionmentioning
confidence: 99%